System effects mapping: a tool for promoting collaborative community ecological action - Baker, Virginia; Walton, Mat; Manning, Suzanne; Ataria, Jamie; Gee, Carla; Taua-Gordon, Robin (Frontiers in Environmental Science, 2024)
Across Indigenous scholarship and environmental sciences there is a growing recognition that community and stakeholder partnerships must underpin and guide the co-production of knowledge to better resolve the complex socio-political issues responsible for the production, and ultimately the mitigation, of pollution. This article reports work that aimed to support shared understanding within community stakeholder partners as part of two larger environmental science projects to understand and reduce pollution within an urban waterway. Utilizing participatory action research, transdisciplinary and translational ecology approaches, the research used System Effects Mapping to visualize a networked understanding of people’s connections to, and valuing of, their local water ways. This led to discussions on ways that community stakeholders felt they could act to improve the environmental conditions, taking into account how actions may interact. While actions identified were not necessarily novel, the approach supported shared understanding between researchers and community stakeholders and shared investment in the knowledge produced. Systems Effects Mapping was a useful method, with the social network output allowing for deeper exploration of transdisciplinary systems change.